UNRAVELING THE PSYCHOLOGICAL CHRONOTOPE IN WILKIE COLLINS’ “THE WOMAN IN WHITE” - Alimova, Irodakhon Zokirjon qizi; To‘rayeva , Bakhor (Educational Research in Universal Sciences, 2024)
“The Woman in White” is a seminal work in Victorian Gothic fiction, characterized by its intricate plot and exploration of psychological depth. Collins’ use of dual temporalities enhances the novel’s complexity, offering readers a multifaceted view of events.Isolation and madness, central themes in the novel, are heightened through the psychological chronotope, creating a chilling and suspenseful atmosphere. The unraveling of secrets within the narrative is facilitated by the psychological chronotope, keeping readers engaged and intrigued throughout the novel.